Student Attitudes Towards Campus Law Enforcement Exploring Issues Of Confidence And Utilization - Ortiz, Vivian J. (2010)
The assessment of citizen attitudes has, in recent decades, become standard practice within the criminal justice system. However, in assessing the criminal justice system, most research has gathered data on the attitudes and perceptions of specific populations within society (i.e. older citizens) and has not really focused on younger age groups, or more specifically, students enrolled in colleges and universities. The present study examined attitudes of college students in the areas of confidence and utilization of campus police. Utilizing a non-random convenience sample of undergraduate and graduate students (N=393) at a large four-year research institution, participants completed a 21-item survey to measure their confidence and utilization of campus police, resources, and services. The results suggest that confidence does not affect utilization of police and students stated they would utilize police despite their confidence level. However, more significantly, students also indicated that while they would utilize police, they reported they had not. As a result, various recommendations were made to improve communications between students and campus police and directions for future research were also noted